FOXP3 expression in T-cell lymphoma: a 47-case study in Edgardo Rebagliati-Martins Hospital; EsSalud, Lima, Peru - Beltrán Gárate, Brady (2009)
Introduction: Foxp3 is a key regulatory gene required for CD25+ and CD4+ regulatory T-cells development and function (Treg), a cell subpopulation specialized in maintaining a balance between immunity and tolerance.Objective: To determine the specificity and prognostic value of Foxp3 expression in T-cell lymphoma.Material and Methods: A retrospective study carried out in 47 patients with T-cell lymphoma in Edgardo Rebagliati-Martins Hospital, EsSalud (Peruvian Social Security), from 1997 to 2004.Results: The expression of Foxp3 in tumoral cells was detected in 8/33 (24%) ATLL (adult t-cell leukemia/lymphoma) cases and in 2/8 (29%) LTPNE cases. There was no statistically significant difference in overall survival between ATLL Foxp3 (+) and ATLL Foxp3 (-). Foxp3 is expressed in different T-cell lymphoma types, and it is not a specific marker for the dientification of ATLL cases.Conclusion: Foxp3 expression can be seen both in ATLL as in LTPNE.